Providing trans-affirming care for sexual assault survivors: An evaluation of a novel curriculum for forensic nurses. (October 2020) - Du Mont, Janice; Saad, Megan; Kosa, Sarah Daisy; Kia, Hannah; Macdonald, Sheila
Abstract: Background: Transgender (trans) persons experience high rates of sexual victimization, often face discrimination by healthcare providers, and may have unique and diverse needs post-victimization. However, there remains a lack of comprehensive trans-specific training among healthcare professionals, including nurses. Objectives: Our primary objective was to develop and evaluate a novel curriculum for its efficacy in improving the competence of forensic nurses in providing sensitive, informed, and appropriate healthcare services for trans survivors of sexual assault. Methods: The curriculum was evaluated among forensic nurses working in sexual assault treatment centres across Ontario, Canada. Forty-seven nurses participated in this study, all of whom were selected by their respective programs to receive in-depth formal Sexual Assault Nurse Examiner training. Changes in participants' perceived expertise and competence in providing trans-affirming care were assessed on a 5-point Likert scale (5 being the highest level) using pre- and post-training questionnaires. Participants were asked to indicate their level of agreement with 31 competency-based statements, which were organized thematically into four domains: Initial Assessment, Medical Care, Forensic Examination, and Discharge and Referral. A clinical vignette assessed participants' demonstrated competence in providing care across four questions. Results: Participants level of expertise improved significantly from pre- to post-training (Mean [ M ] = 1.89, Standard Deviation [ SD ] = 0.84 vs. M = 3.47, SD = 0.62, p < 001), as well as their competence across all content domains: initial assessment ( M = 3.79, SD = 0.63 vs. M = 4.70, SD = 0.31, p < .001), medical care ( M = 3.33, SD = 0.73 vs. M = 4.69, SD = 0.33, p < .001), forensic examination ( M = 3.40, SD = 0.75 vs. M = 4.72, SD = 0.35, p < .001), and discharge and referral ( M = 3.62, SD = 0.80 vs. M = 4.59, SD = 0.40, p < .001). There were also significant improvements in competence associated with the clinical vignette pre- to post- training ( M score = 2.13, SD = 1.06 vs. M score = 3.23, SD = 0.87, p < .001). Conclusions: The success of this curriculum may have relevance to the more than 5000 members of the International Association of Forensic Nurses who practice and support forensic nursing across the globe, as well as to other healthcare professionals. Highlights: Transgender (trans) persons experience high rates of sexual victimization. Comprehensive trans-specific training for healthcare professionals is lacking. Curriculum developed on trans-affirming sexual assault care for forensic nurses. Training improved the perceived and demonstrated competence of forensic nurses. This novel curriculum may have relevance to forensic nursing programs globally.